THE NEED TO IMPROVE THE PROCESS OF DEVELOPING AESTHETIC KNOWLEDGE AND SKILLS IN YOUTH AT A NEW STAGE OF DEVELOPMENT - Kahramаn Mamarahimov (Journals Park Publishing, 2022)
The article provides an in-depth teaching of the theoretical foundations of art in music education and thereby an explanation of the social significance of art and the processes associated with it, the effectiveness of artistic and aesthetic influence, its social significance.
Keywords: music, artistic, aesthetic taste, national tradition, thinking, knowledge, skills, potential.